2008
DOI: 10.1161/circresaha.107.163642
|View full text |Cite|
|
Sign up to set email alerts
|

Sympathetic Activation Causes Focal Adhesion Signaling Alteration in Early Compensated Volume Overload Attributable to Isolated Mitral Regurgitation in the Dog

Abstract: Abstract-We reported that left ventricular (LV) dilatation after 4 weeks of isolated mitral regurgitation (MR) in the dogs is marked by extracellular matrix loss and an increase in adrenergic drive. Given that extracellular matrix proteins and their receptor integrins influence ␤-adrenergic receptor (␤-AR) responses in vitro, we tested whether ␤1-AR activation modulates focal adhesion (FA) signaling and LV remodeling in these same dogs with isolated MR. Normal dogs were compared with dogs with MR of a 4-week d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 49 publications
7
39
0
1
Order By: Relevance
“…The acuity and severity of surgically created MR in animal models versus the physiological response to chronic and gradually worsening MR in humans, along with differences in heart rate response and the use of different beta-blockers in different studies, had precluded firm conclusions on the utility of beta-blockers in this clinical setting [20]. In this context, our study provides insight into the effects of beta-blockers among initially asymptomatic patients with chronic severe nonischemic MR. Our data are consistent with previous studies which suggested an increase in LV dimension with use of beta-blockers [12,17,19], which could accelerate the development of commonly accepted indications for mitral valve surgery.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The acuity and severity of surgically created MR in animal models versus the physiological response to chronic and gradually worsening MR in humans, along with differences in heart rate response and the use of different beta-blockers in different studies, had precluded firm conclusions on the utility of beta-blockers in this clinical setting [20]. In this context, our study provides insight into the effects of beta-blockers among initially asymptomatic patients with chronic severe nonischemic MR. Our data are consistent with previous studies which suggested an increase in LV dimension with use of beta-blockers [12,17,19], which could accelerate the development of commonly accepted indications for mitral valve surgery.…”
Section: Discussionsupporting
confidence: 92%
“…However, this study was too small to meaningfully assess clinical outcomes [8]. Moreover, subsequent studies failed to support a reduction in LV volumes with beta-blockade [15,17]. On the contrary, in an animal model of surgically induced MR, a reduction in heart rate associated with the use of nonselective beta-blockade with carvedilol resulted in significantly decreased LVEF and increased LV volumes and mortality [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with a previous experimental study that β-blockade could cause significant increases in LV dimensions and volumes. 24 Nonbeneficial effect of β-blockade on LV remodeling was also observed in patients with organic MR and normal LV function. 25,26 Furthermore, in a prior study of volume overload caused by aortocaval shunt, LV weight was significantly greater in rats treated with a β-blocker than those without β-blocker treatment.…”
Section: β-Blockade In Chronic Organic Mrmentioning
confidence: 98%
“…2), and myocardial hypertrophy (lengthening) to relieve this stress. 2,5,8,16,17 Because of the geometric stressors of the LV, these changes first appear in the endocardial layers. The endocardial to epicardial myocardial fibers and collagen patterns are aligned on the stress lines of myocardial contractile pathways and collagen is most dense in high-stress and perivascular areas.…”
Section: Overview Of Early (Preclinical) Left Ventricular Remodeling mentioning
confidence: 99%
“…3,4 Microarray pathway analysis demonstrates genes associated with destruction of the interstitial collagen are up-regulated, and pathways associated with maintenance of the extracellular matrix (ECM), 5,6,8 and cardiofibroblasts are down-regulated. 5,8 The increase in cardiomyocyte length and further loss of collagen results in a modest increase in the LV diameter in the mid-ventricular cross-sectional area and a significant increase in total end-diastolic volume. If cardiomyocytes are healthy, the LV contraction results in end-systolic mid-wall dimensions that are close to normal and a total stroke volume that is about twice normal baseline SV.…”
Section: Overview Of Early (Preclinical) Left Ventricular Remodeling mentioning
confidence: 99%